2012
DOI: 10.1002/ejoc.201200440
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of α‐Amino Acids through Samarium(II) Iodide Promoted Reductive Coupling of Nitrones with CO2

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 61 publications
0
6
0
1
Order By: Relevance
“…Recently,t he use of CO 2 as aC 1 source to access a-AAs has attracted increasing attention. [21] Studies by Prikhodko, Walter, Py et al, [22] as well as Radosevich and co-workers [23] and Mita and Sato, [24] focused on the use of (super)stoichiometric metal reductants (SmI 2 ,M g, or Mn) to generate aamino radicals that can react with CO 2 to access a-AAs.A similar strategy was reported by the groups of Yu [25] and Walsh, [26] through the use of PRC.I nt his case,t he key aamino radicals,g enerated after single-electron reduction of imines,a re further reduced to the corresponding carbanion, which is subsequently trapped by CO 2 to yield a-AAs (Scheme 8A).…”
Section: Co 2 As Ac 1 Building Blockmentioning
confidence: 99%
“…Recently,t he use of CO 2 as aC 1 source to access a-AAs has attracted increasing attention. [21] Studies by Prikhodko, Walter, Py et al, [22] as well as Radosevich and co-workers [23] and Mita and Sato, [24] focused on the use of (super)stoichiometric metal reductants (SmI 2 ,M g, or Mn) to generate aamino radicals that can react with CO 2 to access a-AAs.A similar strategy was reported by the groups of Yu [25] and Walsh, [26] through the use of PRC.I nt his case,t he key aamino radicals,g enerated after single-electron reduction of imines,a re further reduced to the corresponding carbanion, which is subsequently trapped by CO 2 to yield a-AAs (Scheme 8A).…”
Section: Co 2 As Ac 1 Building Blockmentioning
confidence: 99%
“…In 2012, Prikhod'ko, Walter,P y, and co-workersr eported that nitrones werea menable to ar eductivec oupling reactionw ith CO 2 in the presence of an excesso fS mI 2 (7.5 equiv; Scheme 8). [8] They found that 50 atm pressure of CO 2 was necessary to suppress the formation of the undesired dimerization product and to obtain the a-aminoa cids in high yields. Fur-Scheme5.Carboxylation reaction promoted by KOtBu and 18-crown-6.…”
Section: Low-valent-metal-promoted Reductive Coupling Reactionsmentioning
confidence: 99%
“…In jüngster Zeit hat die Verwendung von CO 2 als C 1 ‐Quelle für den Zugang zu α‐AS zunehmend an Aufmerksamkeit gewonnen [21] . Studien von Prikhod'ko, Walter und Py [22] sowie Radosevich [23] und Mita und Sato [24] konzentrierten sich auf die Verwendung von (über)stöchiometrischen Metall‐Reduktionsmitteln (SmI 2 , Mg oder Mn) zur Erzeugung von α‐Aminoradikalen. Durch Reaktion mit CO 2 sind so α‐AS zugänglich.…”
Section: Introductionunclassified